MAIL ORDER BRIDE DI INDONESIA: ANALISIS PERSPEKTIF FEMINISME LIBERAL - Diva, Anggia Zara; Shafa Khairunisaa, Selsya; Fuza Adelamajid, Ni Made Cantya; Nataline Deo, Stefany; Nuraeni (Indonesian Association for International Relations, 2024)
This study aims to examine the practice of mail order bride in Indonesia, a practice that involves the choice of Indonesian women who are below the poverty line. Using qualitative methods with secondary data sources and adopting liberal feminist theory, the findings of the analysis show that women involved in this practice tend to be influenced by economic conditions, patriarchal stigma, and lack of access to education. Despite the Indonesian government's efforts through collaboration with women's protection organizations, the complexity of the challenges faced by Indonesian women indicates the need for more concrete and comprehensive measures. Therefore, in order to confront this practice, the Government of Indonesia needs to strengthen the policies that address the root causes of the poverty line among women involved in mail order bride, and ensure equitable welfare for women across Indonesia.